1999
DOI: 10.1097/00042560-199901010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Risk Behavior and HIV Infection Among New Drug Injectors in the Era of AIDS in New York City

Abstract: The new injectors appear to have adopted the reduced risk injection practices of long-term injectors in the city. HIV infection among new injectors, however, must still be considered a considerable public health problem in New York City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 14 publications
1
62
1
3
Order By: Relevance
“…Several studies have found declines in HIV infection rates and risky drug use behaviors among both newer and longer-term injection drug users in New York City during the 1990s. [22][23][24][25][26] National surveillance data suggest that HCV infection incidence in injection drug users is declining throughout the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found declines in HIV infection rates and risky drug use behaviors among both newer and longer-term injection drug users in New York City during the 1990s. [22][23][24][25][26] National surveillance data suggest that HCV infection incidence in injection drug users is declining throughout the United States.…”
Section: Discussionmentioning
confidence: 99%
“…(Am J Public Health. 2001; 91: [23][24][25][26][27][28][29][30] Injection drug users are at high risk for hepatitis C virus (HCV) infection. [1][2][3] Although geographic variation exists, HCV rates among injection drug users are often higher than 60% and in many cities approach 90%.…”
Section: Introductionmentioning
confidence: 99%
“…Injection initiation is a significant event in the life of a drug user since it places the person on a trajectory towards increased health risks, including exposure to bloodborne pathogens, drug overdose, and drug dependence (Chitwood et al, 2000;Des Jarlais et al, 1999;. Studies targeting young injection drug users (IDUs) have focused on factors associated with injection initiation (Fuller et al, 2001(Fuller et al, , 2002Roy et al, 2002;Sherman et al, 2002Sherman et al, , 2005 and the impact of injection initiation on future high-risk injection practices (Crofts et al, 1996;Miller et al, 2006;Novelli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, injecting drug use has been associated with such health and social consequences as depression, suicidal ideation, incarceration, homelessness, Hepatitis C and of most consequential risk, HIV infection (Campbell et al, 2006;Chitwood et al, 2000;Des Jarlais et al, 1999;Havens, Sherman, Sapun, & Strathdee, 2006;Ochoa et al, 2005;Waldrop-Valverde, Ownby, & Kumar, 2005;Wood et al, 2005). Of the 33, 132 cases of HIV infection reported in 2004, 12 percent of adults and adolescents were IDU associated (Centers for Disease Control and Prevention, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a growing body of research has focused on the risks associated with making a transition to injecting among NIUs (Chitwood et al, 2000;De La Fuente, Barrio, Royuela, & Bravo, 1997;Des Jarlais et al, 1999;Neaigus et al, 2006;Neaigus et al, 2001). Many of these studies have found that former injectors are at greater risk of making a transition to injecting compared to those who have never injected.…”
Section: Introductionmentioning
confidence: 99%